MDM2-Mediated Ubiquitination of Angiotensin-Converting Enzyme 2 Contributes to the Development of Pulmonary Arterial Hypertension. Issue 12 (22nd September 2020) - Shen, Hui; Zhang, Jiao; Wang, Chen; Jain, Pritesh P.; Xiong, Mingmei; Shi, Xinxing; Lei, Yuyang; Chen, Shanshan; Yin, Qian; Thistlethwaite, Patricia A.; Wang, Jian; Gong, Kaizheng; et al.
Abstract : Background: Angiotensin-converting enzyme 2 (ACE2) converts angiotensin II, a potent vasoconstrictor, to angiotensin-(1–7) and is also a membrane protein that enables coronavirus disease 2019 (COVID-19) infectivity. AMP-activated protein kinase (AMPK) phosphorylation of ACE2 enhances ACE2 stability. This mode of posttranslational modification of ACE2 in vascular endothelial cells is causative of a pulmonary hypertension (PH)–protective phenotype. The oncoprotein MDM2 (murine double minute 2) is an E3 ligase that ubiquitinates its substrates to cause their degradation. In this study, we investigated whether MDM2 is involved in the posttranslational modification of ACE2 through its ubiquitination of ACE2, and whether an AMPK and MDM2 crosstalk regulates the pathogenesis of PH. Methods: Bioinformatic analyses were used to explore E3 ligase that ubiquitinates ACE2. Cultured endothelial cells, mouse models, and specimens from patients with idiopathic pulmonary arterial hypertension were used to investigate the crosstalk between AMPK and MDM2 in regulating ACE2 phosphorylation and ubiquitination in the context of PH. Results: Levels of MDM2 were increased and those of ACE2 decreased in lung tissues or pulmonary arterial endothelial cells from patients with idiopathic pulmonary arterial hypertension and rodent models of experimental PH. MDM2 inhibition by JNJ-165 reversed the SU5416/hypoxia-induced PH in C57BL/6 mice. ACE2-S680L mice (dephosphorylation at S680) showed PH susceptibility, and ectopic expression of ACE2-S680L/K788R (deubiquitination at K788) reduced experimental PH. Moreover, ACE2-K788R overexpression in mice with endothelial cell–specific AMPKα2 knockout mitigated PH. Conclusions: Maladapted posttranslational modification (phosphorylation and ubiquitination) of ACE2 at Ser-680 and Lys-788 is involved in the pathogenesis of pulmonary arterial hypertension and experimental PH. Thus, a combined intervention of AMPK and MDM2 in the pulmonary endothelium might be therapeutically effective in PH treatment. Abstract : Supplemental Digital Content is available in the text.